2021
DOI: 10.1097/nne.0000000000001116
|View full text |Cite
|
Sign up to set email alerts
|

Universal Design for Learning

Abstract: Background: Blended learning (BL), the combining of face-to-face and online learning, is gaining prominence in nursing education in response to advances in evidence-based learning using technology, the diverse and evolving needs of nursing learners, and unpredictable events impacting nursing education. Problem: Blended learning requires nursing learners and educators to adapt to new modalities and educators to re-envision learning environments. However, BL lacks an educational framework to guide implementati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(9 citation statements)
references
References 15 publications
0
9
0
Order By: Relevance
“…These include pre-registration programs through to specific post-graduate Digital Leadership programs such as provided by the NHS Digital Academy in the United Kingdom. Davis et al (2022) highlight ways to achieve this at pace through blended learning and communities of practice, which help to use both experience and adoption of new technologies as they become relevant to healthcare.…”
Section: Implications For Digital Nurse Leadersmentioning
confidence: 99%
“…These include pre-registration programs through to specific post-graduate Digital Leadership programs such as provided by the NHS Digital Academy in the United Kingdom. Davis et al (2022) highlight ways to achieve this at pace through blended learning and communities of practice, which help to use both experience and adoption of new technologies as they become relevant to healthcare.…”
Section: Implications For Digital Nurse Leadersmentioning
confidence: 99%
“…Undergraduate nursing education programs have undergone substantial changes over the last few years, causing a more significant impact on the quality of health care delivery. Some of the significant changes that occurred over the years include the advancement of nursing education from diplomas to multiple-level degrees, technological advancement, increased leadership roles, and diverse career opportunities in nursing (Davis et al, 2022;Li et al, 2019). These changes made nursing education more accessible to a wide range of learners with diverse characteristics.…”
Section: Background Of the Studymentioning
confidence: 99%
“…Face-to-face learning has been the mainstay of nursing student learning. Blended learning is an approach that utilizes the combination of synchronous or asynchronous online learning and traditional, face-to-face learning (Davis et al, 2022;Li et al, 2019). Innovative web-based instructions offer unparalleled possibilities in the nursing education field.…”
Section: Teaching Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…In recent years, colleges and universities have actively implemented the blended teaching model to achieve personalized education in a variety of ways. In the field of nursing education, the blended teaching can stimulate students’ interest in learning, improve the learning effect and cultivate students’ comprehensive ability [ 7 , 8 , 9 ]. However, other studies have found that there is no statistical difference between the blended teaching group and the traditional teaching group in terms of grades, course satisfaction and independent learning readiness [ 10 ].…”
Section: Introductionmentioning
confidence: 99%